Replacing the transit passage regime with freedom of navigation in the Strait of Malacca: a case study with special reference to the Korea Strait - Mohd Rusli, Mohd Hazmi; Mustafa, Maizatun; Wan Talaat, Wan Izatul Asma (Elsevier, 2013)
The United Nations Convention on the Law of the Sea 1982 (LOSC) prescribes that ships and aircrafts may exercise the unimpeded right of transit passage when navigating or flying over straits used for international navigation. The Straits of Malacca and Singapore are largely categorised as straits that fall under this category. Consistently described as two of the most critical chokepoints in the world, the Straits of Malacca and Singapore are accommodating increasing navigational traffic each year. This has caused difficulties to the littoral States in balancing heavy shipping activities with the protection of the marine environment of these critical straits. This article hence analyse the legal and political implications should the littoral States of the Strait of Malacca, namely Malaysia and Indonesia retract their 12 nautical miles territorial sea claim in the Strait of Malacca to 3 nautical miles, leaving exclusive economic zone (EEZ) or high seas corridor spanning across the Strait, nullifying the application of transit passage regime. At the moment, Japan and South Korea have decided not to extend their territorial claims over the Korea Strait from 3 nautical miles to 12 nautical miles territorial sea limit. As such, this article conducts a specific case study by looking at the arising circumstances should Malaysia and Indonesia follow the Korea Strait approach. This article concludes on whether or not this proposed measure may a viable method to increase the regulatory powers of the littoral States in regulating shipping through the Strait of Malacca.